2009
DOI: 10.1021/jo9014563
|View full text |Cite
|
Sign up to set email alerts
|

Azide Solid Support for 3′-Conjugation of Oligonucleotides and Their Circularization by Click Chemistry

Abstract: A solid support bearing an azido linker was used to synthesize a 3'-azido-alkyl-oligonucleotide by phosphoramidite chemistry. The resulting oligonucleotide was either conjugated by 1,3-dipolar cycloaddition on solid support or in solution with mannose-propargyl derivative and in solution with dansyl propargyl. Besides, after introduction of an alkyne function at the 5'-end, the resulting oligonucleotide bearing both 3'-azide and 5'-alkyne functions was circularized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 62 publications
3
72
0
Order By: Relevance
“…The successful coupling of phosphoramidite 11 with azide containing 7 , followed by in situ oxidation to the phosphate triester was consistent with previous reports in which these functional groups that could react with one another are successfully combined in oligonucleotide synthesis. 38 During the library synthesis the β-cyanoethyl and TBS groups in 12 were cleaved using Et 3 N base. Azide 12 was the last intermediate that was purified prior to library synthesis, as the amine (2) used for preparing the amides obtained via hydrogenation was used crude.…”
Section: Resultsmentioning
confidence: 99%
“…The successful coupling of phosphoramidite 11 with azide containing 7 , followed by in situ oxidation to the phosphate triester was consistent with previous reports in which these functional groups that could react with one another are successfully combined in oligonucleotide synthesis. 38 During the library synthesis the β-cyanoethyl and TBS groups in 12 were cleaved using Et 3 N base. Azide 12 was the last intermediate that was purified prior to library synthesis, as the amine (2) used for preparing the amides obtained via hydrogenation was used crude.…”
Section: Resultsmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22] This aspect was first studied by Sekine et al, who concluded that nucleosides carrying azido groups cannot be adopted in phosphoramidite-based oligonucleotide synthesis because of the interfering Staudinger reaction that takes place between azides and P III derivatives. [24] In their experiment, 2-azido-2Ј-deoxyadenosine was treated with 1.5 equiv.…”
Section: Resultsmentioning
confidence: 99%
“…[19] In line with this interpretation, parallel experiments show that if both the azido and the hydroxyl functions are in the solid phase, the support-bound azides do not disturb the phosphoramidite coupling, and phosphite triester bonds are realized smoothly. [18,22] To the best of our knowledge, the concomitant presence in solution of an alcohol and an azide, both competing for the condensation with an activated phosphoramidite, was not investigated in detail. This issue was briefly reported in a recent paper, in which the conversion of a 4-azido-4-deoxy-d-galactoside into 4-deoxy-d-erythrohexos-3-ulose by reaction with a phosphoramidite reagent and tetrazole as a catalyst, was described.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…and 11, 40 the phosphoramidite derivatives 4,34 15,41 and 16, 42 and the carbohydrate derivatives 2, 43 7, 44 8, 45 and 1216 were synthesized according to reported protocols.Immobilization on Azide Solid Support 1 of 1-O-Propargyl-α-D-mannopyranoside 2 by Cu(I)-Catalyzed 1,3-Dipolar Cycloaddition. An aqueous solution of 1-O-propargylmannose 2 (100 mM, 50 μL), freshly prepared aqueous solutions of CuSO 4 (100 mM, 4 μL), and sodium ascorbate (500 mM, 4 μL), water (42 μL), and MeOH (100 μL) were added to 1 μmol of azide solid support 1.…”
mentioning
confidence: 99%